The Impact of Dehulling and Germination on the Physiochemical, Protein Solubility and Water and Oil Holding Capacities of Yellow Eye Bean (Phaseolus vulgaris L.) Protein Concentrates - Viana, Lauren; English, Marcia (Frontiers in Sustainable Food Systems, 2022)
New pulse varieties including Yellow Eye (YE) beans (Phaseolus vulgaris L.) are a rich source of protein that can be utilized to create value-added protein isolates. Pre-treatments including dehulling and germination have been shown to be effective at improving the nutritional and functional properties of extracted protein isolates. However, the composition and functionality of these protein isolates can vary depending on the pre-treatments and the method of extraction used (salt versus alkaline). Furthermore, little is known about the impact of combining these different processing methods on the properties of YE bean protein isolates. The objective of this study was to evaluate how germination and dehulling pre-treatments influence protein extraction efficiency, physicochemical properties (surface hydrophobicity and intrinsic fluorescence), and the functionality (solubility, oil and water holding capacities) of salt and alkaline extracted protein isolates. Compared to the salt extracted isolates, the alkaline protein isolates exhibited higher protein recovery yields (16-23 % vs. 43-56%) respectively. Conversely, the salt extracted protein isolates exhibited superior functional properties as observed by improved water holding capacities and less variation in their solubilities at different pH values (4 to 10). When the pre-treatments were combined, the salt extracted isolates exhibited improved extraction efficiencies and improved physicochemical characteristics (hydrophobicity and intrinsic fluorescence), whereas the opposite trend was observed in the alkaline protein isolates. The findings from this study provide new evidence to support the hypothesis that protein isolate composition can vary depending on the extraction technique used and the pre-treatment applied. Although the application of dehulling and germination to salt extracted protein isolates was shown to improve or maintain their functionality and physicochemical characteristics. Future research should optimize the salt extraction processes in order to improve overall protein yields.